Joining forces toward proactive elephant and rhinoceros conservation. Issue 1 (16th June 2021) - Vogel, Susanne Marieke; Pasgaard, Maya; Svenning, Jens‐Christian
Abstract: Proactive approaches that anticipate the long‐term effects of current and future conservation threats could increase the effectiveness and efficiency of biodiversity conservation. However, such approaches can be obstructed by a lack of knowledge of habitat requirements for wildlife. To aggregate and assess the suitability of current information available on habitat requirements needed for proactive conservation, we conducted a systematic review of the literature on elephant and rhinoceros habitat requirements and synthesized data by combining a vote counting assessment with bibliometric and term maps. We contextualized these numeric and terminological results with a narrative review. We mapped current methods, results, terminology, and collaborations of 693 studies. Quantitative evidence for factors that influence the suitability of an area for elephants and rhinoceros was biased toward African savanna elephants and ecological variables. Less than one third of holistic approaches considered equal amounts of ecological and anthropogenic variables in their assessments. There was a general lack of quantitative evidence for direct proxies of anthropogenic variables that were expected to play an important role based on qualitative evidence and policy documents. However, there was evidence for a segregation in conceptual frameworks among countries and species and between science versus policy literature. There was also evidence of unused potential for collaborations among southern hemisphere researchers. Our results indicated that the success of proactive conservation interventions can be increased if ecological and anthropogenic dimensions are integrated into holistic habitat assessments and holistic carrying capacities and quantitative evidence for anthropogenic variables is improved. To avoid wasting limited resources, it is necessary to form inclusive collaborations within and across networks of researchers studying different species across regional and continental borders and in the science–policy realm. Abstract : Article impact statement : Habitat assessments should be inclusive, collaborative, and equally value ecological and anthropogenic factors to be proactive. Abstract : Colaboración de Fuerzas hacia la Conservación Proactiva de Elefantes y Rinocerontes Resumen: Los enfoques proactivos que anticipan los efectos a largo plazo de las amenazas a la conservación actuales y futuras podrían incrementar la efectividad y la eficiencia de la conservación de la biodiversidad. Sin embargo, dichos enfoques pueden ser frenados por una falta de conocimiento de los requerimientos de hábitat para la vida silvestre. Para sumar y evaluar la idoneidad de la información disponible sobre los requerimientos del hábitat necesitados para la conservación proactiva realizamos una revisión sistemática de la literatura sobre los requerimientos de hábitat de los elefantes y rinocerontes y sintetizamos los datos combinándolos en una evaluación de conteo de votos con mapas bibliométricos y de términos. Contextualizamos estos resultados numéricos y terminológicos con una revisión narrativa. Mapeamos los métodos, resultados, terminologías y colaboraciones actuales de 693 estudios. La evidencia cuantitativa de los factores que influyen sobre la idoneidad de un área para los elefantes y los rinocerontes estuvo sesgada hacia los elefantes de la sabana africana y las variables ecológicas. Menos de un tercio de las estrategias holísticas consideró cantidades iguales de variables ecológicas y antropogénicas en sus evaluaciones. Hubo una carencia generalizada de evidencias cuantitativas para los indicadores directos de las variables antropogénicas que se esperaba tendrían un papel importante con base en la evidencia cualitativa y los documentos de las políticas. Sin embargo, hubo evidencias de una segregación en el marco conceptual entre los países y las especies y entre la ciencia versus la literatura política. También hubo evidencias de un potencial sin explotar para las colaboraciones entre los investigadores del hemisferio sur. Nuestros resultados indicaron que el éxito de las intervenciones de conservación proactiva puede incrementarse si las dimensiones ecológicas y antropogénicas se integran a las evaluaciones holísticas del hábitat y si se mejoran las capacidades de carga holísticas y las evidencias cuantitativas de las variables antropogénicas. Para evitar gastar los recursos limitados, es necesario formar colaboraciones inclusivas dentro y a lo largo de las redes de investigadores que están estudiando a diferentes especies en las fronteras regionales y continentales y dentro del ámbito de la ciencia política.